Cycloaddition reactions of o-quinone methides with polarized olefins. (April 2021) - Osyanin, Vitaly A.; Lukashenko, Anton V.; Osipov, Dmitry V.
Abstract : The review summarizes and systematizes the [4+2]-cycloaddition reactions of o -quinone methides with electron-rich and electron-deficient olefins. The electron-rich substrates include vinyl ethers, vinyl sulfides, enamines, enamides, enols, furans, benzofurans and indoles, while the electron-deficient substrates are esters of unsaturated carboxylic acids, vinyl azides and quinones. Reactions with push-pull and captodative olefins are also considered. The mechanisms of some reactions are presented. A separate part of the review addresses reactions of p -quinone methides containing an o -hydroxyphenyl substituent at the exocyclic carbon atom, which can isomerize to o -quinone methides. Much attention is paid to oligomerization of o -quinone methides, which proceeds in the absence of active dienophiles or nucleophiles. The bibliography includes 217 references.